MITOS KECANTIKAN DALAM NOVEL KOMPROMI KARYA SOESILO TOER: KAJIAN FEMINISME - Kartini, Kartini; Juanda, Juanda; Suarni, Suarni (Fakultas Bahasa dan Sastra Indoensia, 2020)
The purpose of this study is to describe the beauty myths and the influence of beauty myths on female characters in the Kompromi novel by Soesilo Toer. This research is descriptive qualitative. Data collection techniques in this research is observation and documentation techniques by applying reading and note taking techniques. This research was conducted by indentifying, clarifying, interpreting, and describing beauty myths and the influence of beauty myths on female characters in the Kompromi novel by Soesilo Toer: The study of feminism. Based on research results obtained, in the author’s Kompromi novel raises female characters who are obsessed with beauty myths that women are said to be beautiful when white, slim body shape, sharp nose, like a doll, and decorated, sexy and teasing.